Origami Architecture of an Office Tower in Mega Kuningan, Jakarta - Fauzi, Marsha Dzakira; Ardhiati, Yuke (Journal of Aesthetics, Creativity and Art Management, 2025)
Mega Kuningan as a business district has a future vision. An Application of Postmodern Architecture theory by one of its styles is one choice. This study proposed design aims to redefine conventional office buildings, offering forward-thinking solutions that meet the evolving needs of modern businesses. The increasingly developing economy by created more workers rental offices in tall buildings by innovative workplace. By exploring new design approaches we offering a facade building by inspiring of the origami of architecture folded.